A Method to Evaluate the Evidence Dependability on the Stimulus of Neutrosophic Set - Hepzibah, R. Irene; Leonita, D. (Communications in Mathematics and Applications, 2022)
In evidence theory, basic probability assignment plays an important role. The basic probability assignment is usually provided by experts. The evaluation of evidence dependability is till open issue, when preliminary data is unavailable. In this paper, we propose a new method to evaluate evidence dependability on the stimulus of neutrosophic set. The dependability of evidence was evaluated based on the truth degree between Basic Probability Assignments (BPAs). First, basic probability assignments were revamp to neutrosophic set. By the similarity degree between the neutrosophic set, we can obtain the truth degree between the Basic Probability Assignments. Then dependability of evidence can be computed based on its rapport with supporting degree. Based on the new evidence dependability, we formulated a new method for combining evidence sources with different dependability degrades. Finally, the validity of the proposed method is exemplified by the real life example.
Keywords: Evidence theory; Neutrosophic set; Evidence dependability; Basic probability assignment